KUALITAS CITRA PADA DIRECT DIGITAL RADIOGRAPHY DAN COMPUTED RADIOGRAPHY - Zelviani, Sri (Teknosains: Media Informasi Sains dan Teknologi, 2017)
Abstract : The measurement of image quality on Direct Digital Radiography (DR) and Computed Radiography (CR) had been conducted by using baby phantom as the object with abdomen (AP) examining area. The measurement of image quality was analized using ImageJ software i.e. histogram analysis and SNR (Signal to Noise Ratio) calculation. The results indicate that value of SNR analysis on CR is higher than DR for both measurement results. Gray level distribution of histogram analysis on DR wider than CR.